Prizefighting and Civilization : A Cultural History of Boxing, Race, and Masculinity in Mexico and Cuba, 1840-1940 - LaFevor, David C. (Book collections on Project MUSE., 2020)
In Prizefighting and Civilization: A Cultural History of Boxing, Race, and Masculinity in Mexico and Cuba, 1840-1940, historian David C. LaFevor traces the history of pugilism in Mexico and Cuba from its controversial beginnings in the mid-nineteenth century through its exponential rise in popularity during the early twentieth century.